CRITERIA, LANGUAGE AND THE REVITALISATION OF BLACK THEOLOGY - Brand, G. (Scriptura, 2010)
Drawing on debates within Black Theology, it is possible to identify, inductively, a set of criteria for judging theological constructs, that can be defended both within the tradition of Black Theology and with reference to theology in general. This meta-theological model, when considered against the background of the present South African context - in both its continuity and its discontinuity with the past - reveals not only the continuing relevance of Black Theology, but also some new themes that must be explored using the resources of Black Theology. Among these is language as a "question of power" (Chomsky) - specifically the move from racial to linguistic capitalism as an aspect of the black experience, which has implications, not only for the content, but also for the conduct, of Black Theology during its "revitalisation phase".